An overview on Malaysia's ethics initiatives - Lokman, Asmidar; Talib, Ahmad Tarmizi (2017)
Reforms in the public administration have changed the way how tasks are performed in the public service. The Malaysian public service had gone through various changes in its style of administration. Starting with the traditional public administration then shifted to the New Public Management (NPM) and later to governance. The shift changes the way administration is manoeuvred however it highlighted one common theme to how work should be performed which is through the application of ethics. Ethics is no stranger to the Malaysian public administration as it has been a consistent theme throughout the changes even though it was not highlighted as the main objective of each reform. Thus, this paper aims at overviewing the evolution of ethics initiatives in the Malaysian public administration and some of the challenges it faced.